If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -4x = -6x + 12 Reorder the terms: 20 + -4x = 12 + -6x Solving 20 + -4x = 12 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 20 + -4x + 6x = 12 + -6x + 6x Combine like terms: -4x + 6x = 2x 20 + 2x = 12 + -6x + 6x Combine like terms: -6x + 6x = 0 20 + 2x = 12 + 0 20 + 2x = 12 Add '-20' to each side of the equation. 20 + -20 + 2x = 12 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 12 + -20 2x = 12 + -20 Combine like terms: 12 + -20 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| (n-2)180=60 | | -4+4x+6x=-54 | | 7x+6+6x=110 | | t/-12=-4/15 | | -2*-4=5+8 | | -6+6x-4x=16 | | x^2-4ax-2=0 | | -5x+7+2x=-8 | | 1=5x+3x-7 | | 1=p+12 | | 3*-2=5*4-26 | | -21n=483 | | 3sinx+4cosx^2=0 | | r+2=15 | | -3*-2=x+2 | | 2u+10=26 | | (2x-5)(3x+4)= | | 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 | | 5x^3=85 | | (4y-8)(3y+7)=0 | | w=mxf+eforx | | z(z+7)=0 | | 12x6/6x3 | | -4q-(-7.3)=45.9 |